MANAGEMENT OF UMRAH PACKAGE OPERATIONS: AN ANALYSIS OF UMRAH OPERATING COMPANIES EXPERIENCE - Rofie, Mohamad Khadafi Hj.; Mahmad, Muhamad Amar; Ismail, Nor Hanani Binti; Ahmad, Shukri (CENTRAL ASIA AND THE CAUCASUS, 2024)
In Malaysia, Umrah package operations have recorded a significant increase every year. In the Malaysian context, the Umrah Service Management Manual (Manual Pengurusan Perkhidmatan Umrah, MPPU) serves as a guideline for umrah service operators to assist them in organizing umrah services for Malaysian pilgrims. Besides, the production of this Manual also aims to explain to the reader the orderly and systematic process in the administration and management of umrah. The publication of this Manual is a step by the Department of Awqaf, Zakat, and Hajj [1] to ensure that the umrah management process can be performed professionally and is the best for Muslims. Therefore, this study examines the management of umrah packages based on the Umrah Service Management Manual (MPPU). The study interviewed ten owners of different travel companies or agencies that offer hajj and umrah packages. The content analysis method was used to analyze the findings from the interviews. An analysis was performed on each transcript of the interviews using MPPU as a reference. The findings of the study found that the companies complied with the management guidelines for handling umrah packages as contained in the Umrah Service Management Manual (MPPU).